WEB-BASED DEVELOPMENT IN NIKAH RULINGS: THE INTEGRATION OF ILMU RIJAL IN HADITH HUKUM - Mohamad Hafizuddin Mohamed Najid; Nurul Fathihin Mohd Noor Shah; Manarina Muhamad Nazri; Mohd Parhan Umar; Wan Syamimi Wan Sanusi, (International Prophetic Conference (SWAN) FPQS USIM, 2024)
This research project explores the integration of digital technology in the dissemination and understanding of Islamic jurisprudence, specifically focusing on the rulings of Nikah (marriage) and the application of Ilmu Rijal (the science of narrators) in Hadith hukum (legal rulings derived from Hadith). This introduces the significance of Nikah in Islamic law and the critical role that authentic Hadith play in shaping these rulings. This study identifies challenges in Hadith education, such as limited sources and engagement in learning materials especially in accessing and understanding Nikah rulings, particularly in relation to the credibility and reliability of Hadith narrators. This research aims to develop a web-based system that effectively integrates Aqli and Naqli knowledge, enhancing the teaching and learning of Hadith and the Munakahat topic. The ADDIE model has been applied in the development process involving a detailed analysis of existing resources, user needs, and the integration of Ilmu Rijal with relevant Hadith and Nikah rulings. The platform will be tested by users to assess its effectiveness in enhancing understanding and accessibility. Other than that, the experts will be interviewed to verify the content included in the web based. The web-based platform hopefully can improve the ability of users to access and comprehend Nikah rulings, particularly by offering detailed insights into the reliability of Hadith narrators. This web-based not only aids in scholarly research but also provides a valuable tool for students and the public interested in Islamic law. The web-based emphasizes the importance of leveraging technology to support Islamic legal studies, ensuring that critical information is accessible and accurate. This will make Hadith learning more accessible and engaging, fostering a deeper understanding of the content. The integration of technology with traditional Islamic scholarship is highlighted as a key step toward preserving and disseminating Islamic legal knowledge in the modern era.